STRENGTHENING LITERACY CULTURE AND DEEP LEARNING THROUGH READING CORNER OPTIMIZATION: A COMMUNITY SERVICE PROGRAM AT UPT SDN 6 MENGKENDEK - Lutma Ranta Allolinggi; Theresyam Kabanga; Arshela Tandilola; Septin Pasang (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
The use of reading corners in primary schools is generally limited to providing reading facilities and has not been optimally integrated into the learning process. This condition was also identified at UPT SDN 6 Mengkendek, Tana Toraja Regency, South Sulawesi, Indonesia. This community service program aimed to optimize the use of reading corners as a strategy to strengthen literacy culture while supporting the implementation of deep learning. The program was carried out over three months using a participatory approach involving the principal, teachers, and students. The activities included needs assessment, program planning, reading corner optimization, implementation assistance, and monitoring and evaluation. Program evaluation was conducted through observations, interviews, and documentation. The findings indicated that optimizing the reading corners increased students' engagement in literacy and learning activities. A total of 63% of students consistently and 22% frequently used the reading corners for reading, seeking additional information, participating in discussions, using books as learning resources, and engaging in independent learning. Teachers also reported improvements in students' literacy culture, critical thinking skills, and learning independence. In addition to supporting classroom instruction, the reading corners became a literacy space where students read and discussed books during break times. Overall, the program demonstrates that optimizing reading corners can strengthen literacy culture while fostering a more active, independent, and meaningful learning environment through their integration as learning resources in deep learning.